Permasalahan KTSP Dalam Kebijakan Kurikulum Pendidikan Agama Islam Di Pondok Pesantren - Muhammad Rizki Cahyadi (AR-RASYID : Jurnal Pendidikan Agama Islam, 2021)
Many problems that arise in the field are related to the implementation of the Education Unit Level Curriculum (KTSP), as well as the preparation and implementation of the Islamic religious education curriculum in Islamic boarding schools. For this reason, it is necessary to review government policies related to revamping the Islamic Religious Education curriculum at Islamic Boarding Schools. Some of these policies are; Law No.20 of 2003 concerning the National Education System, Government Regulation No.19 of 2005 concerning National Education Standards, and Government Regulation No.55 of 2007 concerning Religious and Religious Education, and Regulation of the Minister of National Education (Permendiknas) RI No. 6 of 2007 concerning the Amendment to the Regulation of the Minister of National Education of the Republic of Indonesia No. 22,23,24 of 2006 concerning the Implementation of the Curriculum.